2009
DOI: 10.1002/pmic.200900165
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of cell surface proteins in human bone marrow mesenchymal stem cells cultured with or without basic fibroblast growth factor containing medium

Abstract: Mesenchymal stem cells (MSCs) are multipotent cells, which have the capability to differentiate into various mesenchymal tissues such as bone, cartilage, fat, tendon, muscle, and marrow stroma. However, they lose the capability of multi-lineage differentiation after several passages. It is known that basic fibroblast growth factor (bFGF) increases growth rate, differentiation potential, and morphological changes of MSCs in vitro. In this report, we have used 2-DE coupled to MS to identify differentially expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 97 publications
0
18
0
Order By: Relevance
“…F-actin cytoskeleton networks can regulate cellular shape changes and force the migration of MSCs [23]. Therefore, we observed the actin structure by staining cells with rhodamine phalloidin as a probe for filamentous actin after treatments with the FAK or Rho-family GTPase inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…F-actin cytoskeleton networks can regulate cellular shape changes and force the migration of MSCs [23]. Therefore, we observed the actin structure by staining cells with rhodamine phalloidin as a probe for filamentous actin after treatments with the FAK or Rho-family GTPase inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…In a proteomic study using 2DE and LC-MS/MS, Lee at al. [33] found that the addition of 10 ng/mL basic fibroblast growth factor (bFGF) differentially regulated the expression of 15 proteins, of which actin-related protein 2/3 complex subunit 2 (ARPC2), isoform 2 of glial fibrillary acidic protein (GFAP), lamin-A/C (LMNA), ubiquinol-cytochrome c reductase complex core protein 1 (UQCRC1), the multifunctional protein ADE2 (PAICS), F-actin-capping protein subunits alpha-1 (CAPZA1) and alpha-2 (CAPZA1), Septin-2 (SEPT2), and elongation factor 1-gamma (EEF1G) have been upregulated and Myosin regulatory light chain (MRLC2), desmoplakin (DSP), proteasome subunit alpha type 5 (PSMA5), and heat shock protein beta-1 (HSPB1) have been downregulated more than 2-fold. The functional classification of these proteins showed that these proteins mainly belonged to structural and cell morphology regulating groups, indicating that bFGF might regulate MSC differentiation and structure.…”
Section: Proteomics Of Bone Marrow-derived Mscsmentioning
confidence: 99%
“…Proteomics approaches have recently been used to identify cell‐surface markers of stem‐cell function and fate (Cao et al ., ; Sarkar et al ., ). Membrane proteins can be studied by cell‐surface biotinylation followed by liquid chromatography–mass spectrometry/mass spectrometry (LC‐MS/MS) (Lee et al ., ). This approach recently identified the transferrin receptor as a candidate marker of neural stem cells (NSCs) (Cao et al ., ) and defined the membrane proteome of undifferentiated human embryonic stem cells (hESCs) (Sarkar et al ., ).…”
Section: Introductionmentioning
confidence: 97%